Innovative approach to Pb (II) removal using zinc-based MOFs-derived carbon: In-depth analysis of adsorption mechanisms, isotherms, thermodynamics, and kinetics - Samira Ahmadzadeh; Alireza Hemmati (Results in Engineering)
Water contamination by lead is a critical environmental problem due to its toxicity and persistence in industrial effluents. The removal of lead ions from aqueous solutions has become a significant concern for environmental and public health. In this study, we explore the synthesis of carbon derivatives from zinc-based metal-organic frameworks (MOFs) as a potential solution to this issue. The high surface area and porous structure of MOFs make them ideal candidates for adsorbing toxic metals like lead. This research hypothesizes that carbonized MOFs can effectively remove lead ions from contaminated water. To test this hypothesis, carbon derivatives were synthesized through a solvothermal method at 700 °C under a nitrogen atmosphere. The materials were characterized by XRD, FTIR, FESEM, EDX, and BET analyses. The results indicated significant changes in crystallinity and an increase in the specific surface area after pyrolysis. A central composite design (CCD) was employed to study the effects of various factors such as adsorbent dosage (5–25 mg), lead concentration (20–100 mg/L), contact time (10–50 min), and pH (3–7) on the adsorption process. The optimal conditions for lead removal were found to be an initial lead concentration of 80 mg/L, adsorbent dosage of 10 g/L, an equilibrium time of 38 min, and a pH of 6. The experimental data were well-fitted to the Langmuir adsorption model, suggesting a maximum adsorption capacity of 1395.31 mg/g. According to kinetic studies, the best match was given by the pseudo-second-order model (R2 = 0.9993). These findings suggest that carbon derived from zinc-based MOFs is a highly effective adsorbent for the removal of lead from contaminated water.